2014
DOI: 10.4103/0019-5154.143509
|View full text |Cite
|
Sign up to set email alerts
|

A clinical and statistical survey of cutaneous changes in the first 120 hours of life

Abstract: Background:The spectrum of dermatological manifestations during neonatal period varies from transient self-limiting conditions to serious dermatoses; the latter, fortunately few, are disproportionately stressful to the parents, who due to lack of specialized pediatric dermatology clinics frequently get tossed between a dermatologist and a pediatrician.Objectives:This study was formulated to record cutaneous changes over the first five postnatal days of life and to statistically correlate those changes occurrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
14
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 9 publications
9
14
1
7
Order By: Relevance
“…A) presents as erythematous macules, papules or pustules resembling flea bites. In previous reports, [1][2][3][4][5][6][7][8][9]13,[15][16][17][18] the frequency of ETN varied widely between 1.3% and 40.8%; the incidence in our study population was 22.76%. There are conflicting results conserning the predisposing factors.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…A) presents as erythematous macules, papules or pustules resembling flea bites. In previous reports, [1][2][3][4][5][6][7][8][9]13,[15][16][17][18] the frequency of ETN varied widely between 1.3% and 40.8%; the incidence in our study population was 22.76%. There are conflicting results conserning the predisposing factors.…”
Section: Discussionmentioning
confidence: 49%
“…Some studies [10,11] found a significant correlation between the frequency of the lesion and vaginal delivery, whereas another [6] revealed a higher incidence in neonates born by cesarean section. Liu et al [10] and Sadana et al [9] observed an association with primiparity, whereas others [6,7] detected a higher frequency in cases of multiparity. The data relating to the frequency according to gender were also contradictory.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations